A Multi-Target Motor Imagery Training Using Bimodal EEG-fMRI Neurofeedback: A Pilot Study in Chronic Stroke Patients - Lioi, Giulia; Butet, Simon; Fleury, Mathis; Bannier, Elise; Lécuyer, Anatole; Bonan, Isabelle; Barillot, Christian (Frontiers in Human Neuroscience, 2020)
Traditional rehabilitation techniques present limitations and the majority of patients show poor one-year post-stroke recovery. Thus, neurofeedback or Brain Computer Interfaces applications for stroke rehabilitation purposes are gaining increased attention. Indeed, neurofeedback has the potential to enhance volitional control of targeted cortical areas and thus impact on motor function recovery. However, current implementations are limited by temporal, spatial or practical constraints of the specific imaging modality used. In this pilot work and for the first time in literature, we applied bimodal EEG-fMRI NF for upper limb stroke recovery on four stroke patients with different stroke characteristics and motor impairment severity. We also propose a novel, multi-target training approach that guides the training towards the activation of the ipsilesional motor cortex. In addition to fMRI and EEG outcomes, we assess the integrity of the corticospinal tract with tractography. Preliminary results suggest the feasibility of our approach and show its potential to induce an augmented activation of ipsilesional motor areas, depending on the severity and the severity of the stroke deficit. Only the two patients with preserved corticospinal tract and subcortical lesions succeeded in upregulating the ipsilesional primary motor cortex and exhibited a functional improvement of upper limb motricity. These findings highlight the importance of taking in account the variability of the stroke patients’ population and enabled to identify inclusion criteria for the design of future clinical studies.